Productivity of Straw Mushrooms (Volvariella volvacea (Bull.) Fries) in Combination of Straw and Coffee Grounds Growing Media - Irfa Masyura; Samingan Samingan; Wiwit Artika (Universitas Syiah Kuala, 2020)
Substrate of straw mushroom in general are straw. Spent coffee grounds are one of the wastes that can be used as an alternative substrate for straw mushrooms. The purpose of the research are to know the productivity effect of straw mushrooms on spent coffee grounds substrate, as well as to know the optimal comparison of substrate combinations for productivity of straw mushrooms. This research is experimental with a quantitative approach. The design used was a Nonfactorial Completely Randomized Design consisting of 5 treatments and 5 replications. The treatments were 100% straw (P0) as positive control, 75% straw and 25% spent coffee grounds (P1), 50% straw and 50% spent coffee grounds (P2), 25% straw and 75% spent coffee grounds (P3), and 100% spent coffee grounds (P4). Data were analyzed by Analysis of Variants (ANAVA). The results of this research indicate the substrate combination of straw and spent coffee grounds do not affect to productivity (amount) of straw mushrooms. The optimal substrate combination of straw mushrooms are P3 treatment with a combination of 25% straw and 75% spent coffee grounds.